Employee Performance at the Tomohon City Regional Secretariat - Pitoy, Jureyke I.; Tambingon, Henny; Podung, Beatrix J.; Wuryaningtrat, Nikolas F. (International Journal of Information Technology and Education, 2024)
The performance of an organization is very dependent on the performance of its employees, in other words, the performance of employees will contribute to the performance of the organization in which they are located. This means that the behavior of organizational members, both individually and in groups, can provide strength or influence over the organization's performance. The research results show that leadership, organizational culture, and work motivation significantly affect employee performance. Where the significance value (Sig) is less than the significance level (α) and the FCount value is greater than FTable, indicating that the null hypothesis (Ho) can be rejected. Therefore, it can be concluded that employee performance (Y) at the Tomohon City Regional Secretariat is influenced positively and significantly by leadership (X1), organizational culture (X2), and work motivation (X3). Additional analysis shows a strong influence between these variables, with a correlation coefficient (r) of 0.835 and a coefficient of determination (r2) of 69.85%, it can be concluded that leadership, organizational culture, and work motivation positively contribute to employee performance. Good leadership and being a role model, authoritative, responsible, and nurturing which can move employees to improve their performance is supported by an organizational culture that is supportive, open, and focused on common goals as factors that play an important role will stimulate employee work motivation so that it will influence employee performance to be even better. The integration of these variables shows that improving employee performance can be achieved through holistic attention and action towards these factors.